Inflammation induced by Bothrops asper venom: release of proinflammatory cytokines and eicosanoids, and role of adhesion molecules in leukocyte infiltration - Zamunér, Stella Regina (2005)
Bothrops asper venom (BaV) causes systemic and local effects characterized by an acute inflammatory reaction with accumulation of leukocytes and release of endogenous mediators. In this study, the effects of BaV on the release of the cytokines IL-1, IL-6 and TNF-alpha and the eicosanoids LTB4 and TXA2 in the peritoneal cavity of mice were analyzed. We also investigated the participation of beta2 integrin chain, l-selectin, LFA-1, ICAM-1 and PECAM-1 adhesion molecules in the BaV-induced leukocyte accumulation. Levels of proinflammatory cytokines IL-6 and TNF-alpha, as well as eicosanoids LTB4 and TXA2 were significantly increased after BaV injection (250 microg/kg), whereas no increment in IL-1 was observed. Anti-mouse l-selectin, LFA-1, ICAM-1, PECAM-1 and beta2 integrin chain monoclonal antibodies resulted in a reduction of neutrophil accumulation induced by BaV injection compared with isotype-matched control injected animals. These data suggest that BaV is able to induce the activation of leukocytes and endothelium to express adhesion molecules involved in the recruitment of neutrophils into the inflammed site. Furthermore, these results showed that BaV induces the release of cytokines and eicosanoids in the local of the venom injection; these inflammatory mediators may be important for the initiation and amplification of the inflammatory reaction characteristic from Bothrops sp envenomation.